Asclepain cI, a proteolytic enzyme from Asclepias curassavica L., a south American plant, against Helicobacter pylori - Salinas Ibáñez, Ángel Gabriel; Origone, Anabella L.; Liggieri, Constanza S.; Barberis, Sonia E.; Vega, Alba E. (Frontiers in Microbiology, 2022)
Helicobacter pylori is a gram negative bacterium most frequently associated to human gastrointestinal infections worldwide. The increasing occurrence of antibiotic-resistant isolates of H. pylori constitutes a challenge. The eradication of the microorganism is currently being considered as “high priority” by the World Health Organization (WHO). In this context, bioactive compounds found in natural products seem to be an effective therapeutic option to develop new antibiotics against the pathogen. In this study, we investigated the effect of asclepain cI, the main purified proteolytic enzyme of the latex of petioles and stems from Asclepia curassavica L. (Asclepiadaceae), a South American native plant, against H. pylori; in order to obtain a natural therapeutic adjuvant as well as a safe nutraceutical product. Asclepain cI showed antibacterial activity against reference strains and drug-resistant clinical isolates of H. pylori in vitro. A range of minimal inhibitory concentration (MIC) from 1 to 2 µg/mL and minimal bactericidal concentration (MBC) from 2 to 4 µg/mL was obtained respectively. The action of asclepain cI on the transcription of omp18, ureA, flaA genes showed a significant decreased expression of the selected pathogenic factors. Furthermore, asclepain cI did not induce toxic effects at the concentrations assayed. Asclepain cI could be considered a highly feasible option to be used as a natural therapeutic adjuvant and a safe nutraceutical product against H. pylori.